Evaluation of Mobile Phone Addiction Scale Score and It’s Correlation with Craniovertebral Angle and Neck Disability in Young Adults - a Cross- Sectional Analytical Study - Shrikrishna Shinde (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background Worldwide technology and its changes play a major role in each individual?s life. Mobile phone is considered as an important communication tool and became the integral part of the society, it is not only a communication device but it also a necessary social accessory. The bending moment of the head applies pressure on muscles and joints around the cervical vertebra, in addition to active myofascial trigger points of the suboccipital muscle which may induce tension type headaches, neck pain and cervical headaches, while reducing the mobility of the neck. Aim To evaluate mobile phone addiction scale score and it?s correlation with craniovertebral angle and neck disability in young adults. Methods In this cross sectional study, 100 young adults were recruited from medical college. Subjects were evaluated or assessed for mobile phone addiction using mobile phone addiction scale, craniovertebral angle were measured using MB ruler software and neck disablity was assessed using neck disability index. After all measurements were taken, the correlation between mobile phone addiction scale and craniovertebral angle, mobile phone addiction scale and neck disability was carried out. Results Pearson?s correlation coefficient test was conducted between mobile phone addiction scale score and craniovertebral angle (r = -0.6786, p = < 0.0001), mobile phone addiction scale score and neck disability index (r = 0.6170, p< 0.0001) i.e extremely significant. Hence there is a significant correlation between these variables. Conclusion The study demonstrated that there was a significant correlation between mobile phone addiction scale score and craniovertebral angle, mobile phone addiction scale score and neck disability index. Also we found that as highest the mobile phone addiction scale score a young adults had, they are more prone to develop forward head posture and neck pain.